PENERAPAN MODEL PEMBELAJAN PROBLEM SOLVING UNTUK MENINGKATKAN SIKAP ILMIAH DAN HASIL BELAJAR SISWA POKOK BAHASAN ENERGI SISWA KELAS IV SD ISLAM ROUDLOTUL QUR’AN MOJOKERTO - Isma Afifatussa’diyah; Singgih Baktiarso; Traspsilo Prihandono (Universitas Negeri Medan, 2022)
Abstract : The Application Of The Learning Model To Improve Scientific Attitude And Learning Outcomes Of Students Of Class IV Energy Students Of Roudlotul Qur'an Islamic Elementary School, Mojokerto, The purpose of this classroom action research is to find out the improvement of scientific attitudes and student learning outcomes on the subject of energy after applying the Problem Solving Learning Model. This research uses classroom action research with two cycles. Each cycle consists of four stages, namely planning, implementation, observation and reflection. The location of this classroom action research was carried out at the Islamic Elementary School Roudlotul Qur'an Mojokerto, East Java province. The research was carried out in December 2021. The subjects of this research were the fourth grade students of Islamic Elementary School Roudlotul Qur'an Mojokerto, totaling 23 students. The main topic of discussion is about the material